2009
DOI: 10.1007/s00484-009-0230-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of encouraged water drinking on thermoregulatory responses after 20 days of head-down bed rest in humans

Abstract: We tested the hypothesis that encouraged water drinking according to urine output for 20 days could ameliorate impaired thermoregulatory function under microgravity conditions. Twelve healthy men, aged 24 +/- 1.5 years (mean +/- SE), underwent -6 degrees head-down bed rest (HDBR) for 20 days. During bed rest, subjects were encouraged to drink the same amount of water as the 24-h urine output volume of the previous day. A heat exposure test consisting of water immersion up to the knees at 42 degrees C for 45 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Another possible reason for the decreased sweat rate lies in the fluid loss induced by real or simulated weightlessness. Sato 14 and Shibasaki 15 hold this point of view. As described by Hall, 41 the sweat of the human body is originally from the interstitial fluid.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Another possible reason for the decreased sweat rate lies in the fluid loss induced by real or simulated weightlessness. Sato 14 and Shibasaki 15 hold this point of view. As described by Hall, 41 the sweat of the human body is originally from the interstitial fluid.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to the above, results of terrestrial studies of weightlessness have also indicated altered sweating. 11–18 During a 13-day, −6° head down bed rest (HDBR) experiment conducted by the National Aeronautics and Space Administration (NASA), the mean core temperature of subjects for the onset of sweating was increased by 0.28°C, 11,12 suggesting an altered sweat response which had further altered thermal regulation in HDBR simulated weightlessness. Another −6° HDBR experiment conducted by NASA 13 found their subjects started sweating at a lower mean skin temperature and that their normal vasodilation response was impaired slightly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid and dramatic body fluid shifts in space also impair evaporative heat loss. Blunted thirst sensations and lower fluid intakes compound this problem [13,14]. In-flight fluid shifts centralize blood volumes, as a result the body expends more energy to pump blood to the skin surface to enable evaporation.…”
Section: Higher Metabolic Rates/inefficient Body Heat Removalmentioning
confidence: 99%
“…Lower fluid intakes evoke dehydration and cause perspiration rates to decline with longer missions, while sweating in space creates a film over the skin that impairs convective heat loss [10,15]. Thus, astronauts often return to Earth from longer flights with 1-5% body and muscle mass losses, hyperthermic and dehydrated [6,10,[14][15][16][17]. Better in-flight nutritional and hydration strategies must be devised to abate these effects.…”
Section: Higher Metabolic Rates/inefficient Body Heat Removalmentioning
confidence: 99%